The Neumann problem for the Cauchy-Riemann complex - Folland, G. B.; Kohn, Joseph John, 1932- (Annals of mathematics studies ;, 1972)
This book is based on the notes from lectures given by the second author at Princeton University in the year 1970-71, which were subsequently expanded and revised by the first author.